Pengenalan Platform Instagram Sahabat_Riset untuk Membantu Penulisan Tugas Akhir (Skripsi) Mahasiswa - Yaldi, Destri; Selviani, Selviani; Ariati, Jumerli; Nurfadilah, Nurfadilah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
A thesis is a mandatory requirement to obtain a bachelor's degree, however, students consider thesis to be a fear in themselves because the students' understanding is not yet optimal in writing the thesis itself. This service is carried out in order to help students understand thesis writing by optimizing the Instagram platform. This is because as many as 89.15 million Instagram users in Indonesia make it a popular social media among teenagers, including students themselves. The content created will be adjusted to overcome students' difficulties in writing their thesis. Content is in the form of interactive multimedia, where the combination consists of text, images, sound, animation, video and others in an integrated and synergistic manner using Instagram features such as feeds, stories and reels.